MENINGKATKAN PEMAHAMAN MATERI DESSERT MELALUI MEDIA PEMBELAJARAN QUIZIZZ - Aliya, Nabila Ummu; Susilowati, Susilowati; Kelvino , M Kelvino; Fajar, Mundhi (Steam Engineering, 2025)
The aims of this study is to enhance the understanding of vocational high school students in the Culinary Department, Phase E, regarding Dessert material by utilizing Quizizz as an interactive learning medium. The research employs Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data collection was carried out through pre-tests and post-tests to measure students' comprehension improvement. The findings indicate that implementing Quizizz effectively enhances students' understanding, with a learning outcome increase of 16% in the first cycle and 30% in the second cycle. The use of Quizizz not only boosts student engagement in the learning process but also creates a more interactive and enjoyable learning atmosphere. This study proves that integrating technology as a learning medium can be an effective solution to improving education quality, particularly in the culinary field at vocational high schools